2023
DOI: 10.3390/biomedicines11041220
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology of Osteoporosis: Nursing Involvement and Management

Abstract: Osteoporosis is a major public health problem today. We are facing an aging society where the average life expectancy continues to increase. Osteoporosis affects more than 30% of postmenopausal women due to hormonal changes that occur during this time. Postmenopausal osteoporosis is therefore of particular concern. The aim of this review is to identify the etiology, pathophysiology, diagnosis and treatment of this disease and lay the foundation for the role nurses should play in preventing postmenopausal osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Since it has been observed that the incidence of falls is higher in postmenopausal women than in men of the same age, probably as a consequence of decreased estrogen levels on postural stability and potentially muscle strength, exercise is a good strategy to increase muscle strength, resulting in improved posture and balance [17,18].…”
Section: Postmenopausal Osteoporosis and Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has been observed that the incidence of falls is higher in postmenopausal women than in men of the same age, probably as a consequence of decreased estrogen levels on postural stability and potentially muscle strength, exercise is a good strategy to increase muscle strength, resulting in improved posture and balance [17,18].…”
Section: Postmenopausal Osteoporosis and Sarcopeniamentioning
confidence: 99%
“…Numerous studies in both ovariectomized (OVX) mice and women with postmenopausal osteoporosis have shown that exercise reduces bone mineral loss, improves bone microstruc-ture, and static and dynamic balance with increased muscle strength in the upper and lower limbs [18,19]. Nevertheless, it should not be forgotten that patients affected by osteosarcopenia with a very low bone mass and by sarcopenia are fragile and polymorbid, which makes the applicability of exercise in clinical practice complicated and unattainable in severe cases [20].…”
Section: Postmenopausal Osteoporosis and Sarcopeniamentioning
confidence: 99%
“…Many factors ( Figure 2 ), such as genetic susceptibility, endocrine alterations, senescence, nutritional deficiency, and poor lifestyles, have been associated with an increased risk of bone and fragility fractures ( Wang et al, 2023b ; Valenzuela-Martínez et al, 2023 ). For example, aging and age-related disorders may cause an elevated level of pro-inflammatory cytokines, such as IL-6, IL-1β, and TNFα, which contribute to the imbalance of bone homeostasis ( Di Munno and Ferro, 2019 ).…”
Section: The Pathogenesis Of Opmentioning
confidence: 99%
“…In 2010, approximately 22,000,000 women and 5,500,000 men had OP in the European Union, and the costs for the incidents and prior fragility fractures are estimated at € 37 billion (Svedbom et al, 2013). It has been reported that more than 1/3 of adult women and 1/5 of adult men may experience one or more fragility fractures in their lifetime (van Staa et al, 2001). OP and the fragility fracture have posed challenges to individuals and society.…”
Section: Introductionmentioning
confidence: 99%